P‐209: Late‐News Poster: Influence of Drying and Mixing Condition of the Host Materials on the Lifetime of Solution‐Processed OLEDs. Issue 1 (29th May 2019) - Lee, Ja Yeon; Kim, Nam Su; Suh, Min Chul
Abstract : In order to investigate the influence of drying condition and host mixing ratio, we fabricated the solution processed OLEDs with two different host materials and Ir(mppy)3 as a green phosphorescent dopant. From this study, we found that the device lifetime of solution‐processed OLEDs was realized by controlling the recombination zone as well as drying temperature.